An innovative in-situ DRAINage system for advanced groundwater reactive TREATment (in-DRAIN-TREAT). (May 2021) - Bortone, I.; Santonastaso, G.; Erto, A.; Chianese, S.; Di Nardo, A.; Musmarra, D.
Abstract: The removal of groundwater contamination is a complex process due to the hydro-geochemical characteristics of the specific site, related maintenance and the possible presence of several types of pollutants, both organic and inorganic. In recent decades, there has been an increasing drive towards more sustainable treatment for contaminated groundwater as opposed to "intensive" treatments, i.e. with high requirements for onsite infrastructure, energy and resource use. In this study, a new remediation technology is proposed, combining the use of advanced drainage systems with adsorption processes, termed "In-situ reactive DRAINage system for groundwater TREATment" (In-DRAIN-TREAT). By taking advantage of the groundwater natural gradient, In-DRAIN-TREAT collects the contaminated groundwater via a drainage system and treats the polluted water directly into an active cell located downstream, avoiding external energy inputs. Preliminary results indicate the applicability and high efficiency of In-DRAIN-TREAT when compared with a permeable reactive barrier (PRB). In-DRAIN-TREAT is applied to remediate a theoretical aquifer with low permeability, contaminated by a 13 m wide hexavalent chromium (Cr VI ) plume. This is achieved in less than a year, via a drain DN500, 32 m long, a 30 m 3 treatment cell filled with activated carbon and no energy consumption. A comparison with permeable barriers also shows a preliminary 63% volume reduction, with a related 10% decrease of remediation costs. Graphical abstract: Image 1 Highlights: In-DRAIN-TREAT is a passive in-situ treatment technique for polluted groundwater. In-DRAIN-TREAT allows for a sustainable remediation of low permeability aquifers. An aquifer contaminated by hexavalent chromium is considered as case study. Pollutant transport and adsorption treatment are numerically evaluated via a 3D model. Compared with PRBs, In-DRAIN-TREAT reduces treatment volume and remediation costs.